Research on Open-Source VoIP Technologies for NGN Service Platform Deployment - Lei Xia; Shaomin Wang; Qingfeng Zhong (Dianxin kexue)
Open-source VoIP technologies can be employed to setup VoIP platforms by deploying open-source software on x86 servers, which have many advantages such as low cost, flexibility and openness. The usage of open-source VoIP technologies in NGN service platform deployment helps to reduce carrier's investment, shorten service deployment cycle and improve the duplicability of service platform. In the paper, the architecture of NGN service platform deployed by open-source VoIP technologies is proposed based on comprehensive survey and detailed analysis. A typical example is also provided to evaluate the feasibility and advantages of the proposed NGN service platform deployment method.